Catheter ablation for atrial fibrillation in left ventricular assist device: A case report. Issue 25 (25th June 2021) - Chung, Yu Jin; Choi, Jin-Oh; Park, Kyoung-Min
Abstract: Introduction: Mechanical circulatory support such as the left ventricular assist device (LVAD) has become widely implemented in the treatment of end-stage heart failure, whether as bridge-to-transplant or as destination therapy. The hemodynamic effects of arrhythmia on LVADs and its management are significant in determining the long-term outcome of these patients. Both atrial arrhythmia and ventricular arrhythmia are commonly seen after implantation of the device. There are no strict guidelines, however, on the need for intensive management of arrhythmias in LVAD. In this case report, we present a patient with new onset atrial fibrillation after LVAD implantation which leads to acute decompensating heart failure. The patient was treated with catheter ablation. The intervention demonstrated positive outcomes for this patient. Patient concerns: The patient was a Korean male, who presented with dyspnea, fatigue and generalized edema after persistent atrial fibrillation precipitated by implantation of the left ventricular assist device. Diagnosis: The patient was diagnosed with acute decompensating heart failure that was aggravated by recurrent atrial arrhythmia. Intervention: We attempted to relieve symptoms of right ventricular dysfunction by method of strict rhythm control in this patient. The patient underwent radiofrequency catheter ablation for recurrent atrial fibrillation. Outcome: The patient showed improved clinical symptoms, BNP levels, and echocardiogram parameters immediately after the procedure as well as during long term outpatient follow up. Conclusion: In this case report, we present the first successful case in Korea of atrial fibrillation in LVAD treated with catheter ablation. This case suggests setting catheter ablation as a routine first-line treatment for atrial arrhythmia in LVAD patients, especially when the arrhythmia predisposes the patient at risk for decompensating heart failure.